Long-Term Influence of Coal Mining Activities on Physico-Chemical and Hydraulic Properties of Sandy Tropical Soils - Paul Omaye Joseph; Lois Ekwuojo Abraham; Chika Mike Jidere; Chioma Lilian Ugwuoju; Sunday Ewele Obalum (AgroEnvironmental Sustainability)
Long-term surface coal mining near agricultural zones can degrade arable land and reduce soil productivity. This study evaluated the effects of extended coal mining on sandy soil properties in three mining areas of Ankpa LGA, Kogi State, Nigeria—Okaba-Odagbo (55 years), Okobo-Enjema (12 years), and Onupi (9 years). Soil samples were collected from both mining sites and adjacent fallow (arable) lands and analyzed using standard methods. Statistical comparisons were made using t-tests and Pearson correlation. Across all locations, mining significantly influenced (p < 0.05) soil pH and bulk density. Mining sites showed lower pH (t = –2.49) and higher bulk density (t = 2.35) compared to fallow lands. Site-specific analysis revealed pronounced effects only at Okaba-Odagbo, where the longest mining history corresponded with increased clay content and bulk density (t = 5.00 and 5.69, respectively). No significant differences were observed at Okobo-Enjema and Onupi. When averaged across locations, mining sites had slightly higher values for clay content (10.68%), soil organic carbon (1.81%), exchangeable sodium (0.38 cmol/kg), porosity (0.44), water holding capacity (20.94%), and saturated hydraulic conductivity (56.66 cm/h) compared to fallow lands. The reduced pH at mining sites was linked to sodium and clay enrichment and loss of base-forming elements, while higher bulk density was attributed to decreased macro-aggregation. The findings suggest that coal mining alters the physical and chemical properties of tropical sandy soils, leading to acidification and compaction, which can impair soil quality, permeability, and long-term agricultural productivity.